Visualization of ciliary body structures after preoperative anti-inflammatory in rhegmatogenous retinal detachment complicated by choroidal detachment (Ukrainian Journal of Ophthalmology, 2026)
Background: Rhegmatogenous retinal detachment (RRD) can be complicated by choroidal detachment (CD). The state of the ciliary body in patients with RRD may indirectly indicate active intraocular inflammation.Purpose: To investigate ciliary body dimensions in RRD complicated by CD after preoperative anti-inflammatory treatment.Materials and Methods: This study included 31 RRD+CD patients (31 eyes) with an intact fellow eye who were under observation. Before the vitrectomy, they received 4-mg intravitreal triamcinolone (IVT), either alone or in combination with 0.5 to 0.8 mL of perfluorpropane. Near-infrared transpalpebral transillumination (NIR TPT) and ultrasound biomicroscopy (UBM) of anterior eye structures were performed before and 1, 2, 3 or 4 days after preoperative intravitreal therapy.Results: Mean baseline width and mean baseline thickness of the pars plicata in eyes with combined RRD and CD were statistically significantly greater than in intact fellow eyes (2.4 ± 0.1 mm versus 1.9 ± 0.1 mm, P = 0.01, and 0.83 ± 0.1 mm versus 0.65 ± 0.1 mm, P = 0.02, respectively). Mean post-treatment pars plana width in the affected eyes having axial length > 25.0 mm was 4.74 ± 0.63 mm, and the percentage of these eyes was 64.5% among eyes with combined RRD and CD. Mean thickness and mean width of the pars plicata in the affected eyes after treatment were 2.2 ± 0.1 mm и 0.66 ± 0.1 mm, respectively.Conclusions: In eyes with combined RRD and CD, pars plicata width and thickness were greater than in intact fellow eyes. Ciliary body detachment tends to occur in longer eyes (therefore, those with a greater pars plana width) with RRD. In eyes with combined RRD and CD, there was evidence of re-attachment of the pars plana as well as reduction in pars plicata thickness and width after preoperative anti-inflammatory treatment.
Keywords: rhegmatogenous retinal detachment; ciliary body; infrared radiation; transillumination